Why Reforming foreign Aid is Critical to the Future of Africa, Africans & Their Wildlife - Paul Andre DeGeorges (Global Journal of Ecology - Peertechz Publications, 2020)
The following is a policy document based upon 30 years being involved in Sub-Saharan African conservation, advising African Governments, the U.S. Government and the hunting/conservation communities on the major issues holding back the economic development of the region and ultimately the future of its much revered mega-fauna.  Ultimately, to save Africa's wildlife, we must provide a viable future for the people living with the wildlife. Currently, this is not the case. The current situation is explained with accompanying photographs that support these observations. Foreign aid as currently practiced has failed to achieve these goals. Reasons for this failure are discussed and recommendations made so that foreign aid can play a major role in changing the face of Africa by giving its people and in turn their wildlife a viable future.